1993
DOI: 10.1063/1.108857
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic growth of carbon microtubules with fullerene structure

Abstract: Domain growth kinetics in La0.89Sr0.11MnO3 single crystal studied by piezoresponse force microscopy J. Appl. Phys. 112, 052019 (2012) Understanding on the current-induced crystallization process and faster set write operation thereof in non-volatile phase change memory Appl. Phys. Lett. 100, 063508 (2012) Growth of single-crystalline cobalt silicide nanowires with excellent physical properties J. Appl. Phys. 110, 074302 (2011) Growth of thick heavily boron-doped diamond single crystals: Effect of microwave pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
152
0
7

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 366 publications
(161 citation statements)
references
References 12 publications
2
152
0
7
Order By: Relevance
“…The use of graphite as a support is particularly interesting despite leading to the formation of disordered carbon nanostructures, in agreement with studies by Yacamán et al 25 The ease with which one can cleave relatively few graphitic layers affords facile sample preparations for TEM studies. This is seen in Figure 5, in which a bamboo-like carbon nanotube is imaged at various magnifications.…”
Section: Resultssupporting
confidence: 70%
“…The use of graphite as a support is particularly interesting despite leading to the formation of disordered carbon nanostructures, in agreement with studies by Yacamán et al 25 The ease with which one can cleave relatively few graphitic layers affords facile sample preparations for TEM studies. This is seen in Figure 5, in which a bamboo-like carbon nanotube is imaged at various magnifications.…”
Section: Resultssupporting
confidence: 70%
“…The minimal tube diameter that can be so achieved is that of the catalytic particle. Several authors [12][13][14][15][16][17] tried to adjust parameters such as the catalyst composition and the reaction atmosphere to maximize the nanotube yield and to minimize the tube diameter. Ivanov et al 16 have reported very small amounts of thin tubes (4 nm), and tubes up to 60 mm long, but they point out that the longest tubes are also the thickest.…”
Section: Open Archive Toulouse Archive Ouverte (Oatao)mentioning
confidence: 99%
“…Even though many synthetic methods are known for carbon materials, most of them still require harsh and rather expensive processing conditions such as very high temperatures, arc discharge, or decomposition from the plasma or gas phase [4][5] [6].…”
Section: Introductionmentioning
confidence: 99%